URGENSI KOMUNIKASI INTERPERSONAL PUSTAKAWAN TERHADAP PELAYANAN PEMINJAMAN KOLEKSI PERPUSTAKAAN UNIVERSITAS ANDALAS - Leni Marsih; Ernita Arif; Sarmiati Sarmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This article discusses the communication skills of librarians at the Andalas Padang University Library. The purpose of this study was to analyze the implementation of librarian interpersonal communication to users in providing collection lending services. This study uses a qualitative descriptive method with a qualitative approach. Data collection was carried out through complete participatory observation, namely the researcher was fully involved in several activities carried out by the informants. In addition, researchers also conducted in-depth interviews with librarians and students who act as users in order to strengthen the data in the study. In addition, researchers also use the method of documentation through previous research, manuals and various literatures related to research. Two findings were obtained from these results. First, the lack of use of written verbal communication by new students so that they do not have an understanding of the use of collection lending services. Second, the comparison of the number of officers in loan services with the users they face per day is inadequate.